Admittance to specialized palliative care (SPC) of patients with an assessed need: a study from the Danish palliative care database (DPD). (2nd September 2017) - Adsersen, Mathilde; Thygesen, Lau Caspar; Neergaard, Mette Asbjoern; Bonde Jensen, Anders; Sjøgren, Per; Damkier, Anette; Groenvold, Mogens
Abstract: Background: Admittance to specialized palliative care (SPC) has been discussed in the literature, but previous studies examined exclusively those admitted, not those with an assessed need for SPC but not admitted. The aim was to investigate whether admittance to SPC for referred adult patients with cancer was related to sex, age, diagnosis, geographic region or referral unit. Material and methods: A register-based study with data from the Danish Palliative Care Database (DPD). From DPD we identified all adult patients with cancer, who died in 2010–2012 and who were referred to and assessed to have a need for SPC ( N = 21, 597).The associations were investigated using logistic regression models, which also evaluated whether time from referral to death influenced the associations. Results: In the adjusted analysis, we found that admittance was higher for younger patients [e.g., 50–59 versus 80 + years: odds ratio (OR) = 2.03; 1.78–2.33]. There was lower odds of admittance for patients with hematological malignancies and patients from two regions: Capital Region of Denmark and Region of Southern Denmark. Lower admittance among men and patients referred from hospital departments was explained by later referral. Conclusions: In this first nationwide study of admittance to SPC among patients with a SPC need, we found difference in admittance according to age, diagnosis and region. This indicates that prioritization of the limited resources means that certain subgroups with a documented need have reduced likelihood of admission to SPC.